Power Loss Analysis to Overcome End Voltage DropAE005 Substation Golewa ULP Bajawa Feeder - I Ketut Aris Setiawan Giri; I Wayan Suriana; I Wayan Dikse Pancane; I Wayan Sukadana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Voltage drop at the feeder end is one of the problems that often occur in electrical power distributionsystems, especially in networks with increasing loads. This study aims to analyze the power lossesand the relationship between load conditions, network length, and the ability of the substation tomaintain the voltage profile at the AE005 Substation of Golewa Feeder, ULP Bajawa. The analysismethod used technical calculation of power losses, evaluation of load currents, and simulation ofvoltage profiles under several operating conditions to identify the dominant factors causing voltagedrops. Based on the measurement results, the AE005 substation experienced a transformer load of127.99% and a voltage drop of up to 22.9%, exceeding the standard limit of SPLN No.72:1987 whichallows a maximum drop of 4%. To overcome this, a load breakage strategy was carried out to theAE023 substation with a capacity of 25 kVA. The results of the analysis showed that after the loadbreak, the load of the AE005 transformer dropped to 67.62% and the AE023 increased to 81.88%,while the maximum voltage drop value dropped to below 5%. Thus, load breakage has proven to beeffective in reducing power losses and improving voltage quality in the distribution network.